INTEGRASI PEMBELAJARAN MAKE A MATCH DAN MIND MAP UNTUK MENINGKATKAN PENGETAHUAN DANAU LIMBOTO PADA MATA PELAJARAN MULOK SISWA KELAS V - Salehudin SP Sautu; Razak Umar; Dewi Darmiyani Napu (Al-mujahidah, 2026)
This study aims to determine how to improve students' knowledge in Mulok lessons using the make a match and mind map learning model and whether there is an increase in students' knowledge in Mulok learning for grade V using the make a match and mind map learning model at SDN 11 Limboto. The method used in this study is the classroom action research (CAR) method. This research was conducted at SDN 11 Limboto. The subjects of this study were 30 fifth grade students. Data collection techniques used were observation, field notes, interviews, and tests. Data analysis techniques used were quantitative and qualitative. The results of this study indicate that students' knowledge before the application of the Make A Match and Mind Map learning model had not reached the KKTP. After the application of the Integration of the Make A Match and Mind Map learning model, students' knowledge increased, as seen in the increase in completeness in the pre-cycle from 26% to 50% in cycle I and in cycle II to 86%. Thus, students' knowledge and analysis of observation sheets increased in a better direction with the application of the integration of the make a match and mind map learning model.